Redesain Terminal Tipe A Poris Plawad di Kota Tangerang dengan Tema Arsitektur Hijau - Lusifa Hafi Tamiyati (Fakultas Teknik - Universitas Bung Karno, 2023)
Plawad Terminal is a type A bus terminal which still serves public transportation vehicle mobility in the area around Cipondoh Tangerang District. The potential for passenger mobility and environmental conditions are sufficient to support its existence as a regional transportation facility. Currently, the physical and functional condition of the terminal does not meet the passenger and vehicle service requirements, so a redesign program is needed. The redesign program takes the theme of green architecture as part of improving the quality of the terminal, users and the surrounding environment. The problems raised are: (1) How does the terminal design concept accommodate passenger needs and vehicle movement? (2) How is the green architecture theme applied in building design? The discussion refers to a qualitative analytical-descriptive approach which is based on a theoretical framework and applied to design. From the results of the discussion, a design direction can be formulated, namely: (1) The design is focused on arranging the optimization layout for ease of vehicle movement and passenger space facilities which refer to the principles of walk, transit and connected (2) The design concept refers to energy conservation efforts through shape and spatial layout. Building.